Oral manifestations in human immunodeficiency virus infected patients - Sen Sumit; Mandal Sukanta; Bhattacharya Sourav; Halder Saswati; Bhaumik Parna (Wolters Kluwer Medknow Publications, 2010)
Background: Oral lesions are common among Human Immuno deficiency Virus (HIV)-positive patients. The pattern of oral features in these persons may differ in separate settings. Aims: To find out the spectrum of oral manifestations among a section of seropositive individuals attending the antiretroviral therapy (ART) centre of a referral hospital. Materials and Methods: A total of three hundred and twenty-one newly diagnosed seropositive patients were enrolled in this study. Of these, ninety-four patients who demonstrated lesions related to the oral cavity were examined intra-orally by a clinician. HIV testing was done with ELISA and CD4 counts were measured with the help of fluorescence activated cell sorter (FACS) system. Results: Fifty-four respondents presented exclusively with oral lesions. Candidiasis patients were the largest group (38.30%). Conclusion: HIV disease presents a plethora of oral manifestations, which provide valuable diagnostic and prognostic information.